2018
DOI: 10.3390/nu10101494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera Leaf Powder on Postprandial Blood Glucose Response: In Vivo Study on Saharawi People Living in Refugee Camps

Abstract: The hypoglycemic effect in humans of Moringa oleifera (MO) leaf powder has, to date, been poorly investigated. We assessed the chemical composition of MO leaf powder produced at Saharawi refugee camps, its in vitro ability to inhibit α-amylase activity, and its sensory acceptability in food. We then evaluated its effect on postprandial glucose response by randomly administering, on 2 different days, a traditional meal supplemented with 20 g of MO leaf powder (MOR20), or not (control meal, CNT), to 17 Saharawi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 42 publications
(54 reference statements)
0
64
0
6
Order By: Relevance
“…In addition, a decrease in the mean glycemic response was found with the meal containing moringa leaf powder (268 ± 18 mg/dl) as compared with control meal (296 ± 17 mg/dl) in the diabetic subjects. However, due to the poor taste and acceptability of the dose used (20 g, equivalent to 8% of the meal's weight), the authors suggested that lower doses of moringa leaf powder should be used in future studies, along with preliminary sensory evaluation tests to determine the tolerable dose (Leone et al, ).…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a decrease in the mean glycemic response was found with the meal containing moringa leaf powder (268 ± 18 mg/dl) as compared with control meal (296 ± 17 mg/dl) in the diabetic subjects. However, due to the poor taste and acceptability of the dose used (20 g, equivalent to 8% of the meal's weight), the authors suggested that lower doses of moringa leaf powder should be used in future studies, along with preliminary sensory evaluation tests to determine the tolerable dose (Leone et al, ).…”
Section: Human Studiesmentioning
confidence: 99%
“…However, due to the poor taste and acceptability of the dose used (20 g, equivalent to 8% of the meal's weight), the authors suggested that lower doses of moringa leaf powder should be used in future studies, along with preliminary sensory evaluation tests to determine the tolerable dose (Leone et al, 2018).…”
Section: Human Studiesmentioning
confidence: 99%
“…Source: Chelliah et al (); Leone et al (); Amabye (); Ogbe and Affiku (); Moyo, Masika, Hugo, and Muchenje (); Teixeira et al (); Leone et al (); Valdez‐Solana et al ().…”
Section: Resultsmentioning
confidence: 99%
“…MO is outstanding for its therapeutic behavior and may utilized be for the traditional treatment of Diabetes mellitus (Konmy, Olounlade, Allou, Azando, & Hounzangbe‐Adote, ; Leone et al, ). Antihyperglycemic (Divi, Bellamkonda, & Dasireddy, ; Jaiswal, Rai, Kumar, Mehta, & Watal, ) and hypoglycemic (Ajit, Choudhary, & Bandyopadhyay, ; Tende, Ezekiel, & Dikko, ) activities of leaves might be presumably because of the presence of terpenoids and flavonoids, which involved in stimulation of ß cells and resulting discharge of insulin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation